Modification of Leather Split by In Situ Polymerization of Acrylates - Weixing Xu; Jianfei Zhou; Ya’nan Wang; Bi Shi (International Journal of Polymer Science)
Leather split, the byproduct of leather manufacture, possesses low utility value because it has loose weave of collagen fibers and weak mechanical strengths. Herein, a practical and convenient method for increasing strengths of leather split was developed by one-step in situ polymerization. The structures and properties of polyacrylate/leather split composites were systematically investigated. The results suggested the monomers with an α-methyl and a proper straight-chain ester group, such as nBMA, can effectively modify the leather split. For leather split with a thickness of 1.6 mm, the rational processes for preparation of polyacrylate/leather split composite are that monomer and split were stirred in a drum for 4 hours for full permeation and then the split was heated in anaerobic condition at 45°C for 30 min. The tensile strength, tear strength, and elongation at break of the optimized PnBMA/split composite were 18.72 MPa, 62.73 N/mm, and 46.02%, respectively. With these mechanical properties, the split after modification can be well used as leather for making shoes, bags, gloves, and clothing.